PERBEDAAN PENGARUH PENDEKATAN PEMBELAJARAN PRAKTIK DRILL DAN BERMAIN TERHADAP HASIL TEMBAKAN BEBAS BOLABASKET - WISNU MAHARDIKA (Jurnal Ilmiah Spirit, 2013)
This research aims to find out: (1) the difference effect of drill practice and games to the basketball free throw result, (2) the interaction effect between drill practice and games to the basketball free throw result. Â  This research employed an experimental method with pretest-posttest design. The population of the research in the study were the male of Sport and Health Education of Teaching and Learning Faculty of Surakarta Tunas Pembangunan University, as many as 60 students. The sampling technique was purposive random sampling. The data analysis prerequisite test was done using the sample normality test (Lilliefors test with Î± = 0.05%) and variance homogeneity test (Bartlett test with Î± = 0.05%). Â  Based on the result of the analysis, conclusions are drawn as follows: (1) There is a significant difference drill practice and games to the basketball free throw result. (2) The effect of drill practice is better than that games practice to the basketball free throw result.